2017
DOI: 10.1002/brb3.625
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between cardiorespiratory fitness, hippocampal volume, and episodic memory in a population at risk for Alzheimer's disease

Abstract: IntroductionCardiorespiratory fitness (CRF) has been shown to be related to brain health in older adults. In individuals at risk for developing Alzheimer's disease (AD), CRF may be a modifiable risk factor that could attenuate anticipated declines in brain volume and episodic memory. The objective of this study was to determine the association between CRF and both hippocampal volume and episodic memory in a cohort of cognitively healthy older adults with familial and/or genetic risk for Alzheimer's disease (AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 78 publications
2
41
0
1
Order By: Relevance
“…A practical implication of V̇O 2peak measurement error in the oldest adults of a given study sample is misrepresentation of relationships between CRF and brain health outcomes; relationships which may be better explained by age. In our previous work that employed a smaller sample, we demonstrated that participants who did not satisfy peak effort criteria were statistically older ( d = .69; p < .05), displayed poorer episodic memory ( d = .50; p < .05), and had non-significant smaller hippocampal volumes ( d = .42; p = .06) than those who satisfied criteria [36]. As expected, age was significantly and negatively associated with both outcomes of interest, memory and hippocampal volume.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A practical implication of V̇O 2peak measurement error in the oldest adults of a given study sample is misrepresentation of relationships between CRF and brain health outcomes; relationships which may be better explained by age. In our previous work that employed a smaller sample, we demonstrated that participants who did not satisfy peak effort criteria were statistically older ( d = .69; p < .05), displayed poorer episodic memory ( d = .50; p < .05), and had non-significant smaller hippocampal volumes ( d = .42; p = .06) than those who satisfied criteria [36]. As expected, age was significantly and negatively associated with both outcomes of interest, memory and hippocampal volume.…”
Section: Discussionmentioning
confidence: 97%
“…no specified criteria)[12, 32, 33], using one physiological variable (i.e. HR, RER)[13, 34, 35], or reporting some combination of variables [14, 36, 37]. For this project, we chose the ACSM guidelines because they provide an empirically established standard for CRF testing [28].…”
Section: Discussionmentioning
confidence: 99%
“…Research demonstrates that physical activity is associated with enhanced memory function (Crush & Loprinzi, ; Frith, Sng, & Loprinzi, ; Loprinzi, Edwards, & Frith, ; Loprinzi & Kane, ; Sng, Frith, & Loprinzi, ), with fewer studies examining the effects of cardiorespiratory fitness on memory function (Dougherty et al., ; Hayes, Hayes, Cadden, & Verfaellie, ). Specific focus on cardiorespiratory fitness is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiorespiratory fitness (CRF), an index of habitual physical activity, has been associated with preserved cognitive function and brain structure in older adults [ 10 , 20 , 21 , 25 , 27 , 38 ]. It has also been associated with a lower risk of dementia in the elderly [ 14 , 18 , 46 ].…”
Section: Introductionmentioning
confidence: 99%